Investigation on some main glycosides content of Stevia rebaudian B. under different concentrations of commercial and synthesized silver nanoparticles - zohreh majlesi; Moazzameh Ramezani; Mahyar Gerami (Mazandaran University of Medical Sciences, 2018)
Stevia rebaudiana B. extract as a low-calorie sweetener has gained worldwide approval. Synthesized nanoparticles by plant have been used in different programs such as medical, pharmaceutical and agricultural fields. Here, we report the increase of the main glycosides of stevia plant with silver nanoparticles (AgNPs) treatment. This fact has stimulated research on the analysis and comparison of different concentrations of commercial and synthesized AgNPs on the glycosides of stevia plant by high-performance liquid chromatography (HPLC). After AgNPs synthesis, spectrum absorption of extracts was analyzed in different ranges from 300 to 700 nm and the maximum peak was observed at 420 nm. Transmission electron microscopy (TEM) micrograph of synthesized AgNPs from Stevia rebaudiana extract showed spherical shape with the size of 25 nm. A comparison between quantities of glycoside by HPLC under both treatments of AgNP exhibited that synthesized AgNPs were more effective than commercial AgNPs on stevioside and then rebaudioside. On the other hand, results showed that increasing AgNP concentration in both treatments will lead to glycoside content enhancement. Overall, significant changes were observed in the glycosides in plants under synthesized and commercial AgNP treatment that could be used to create plants with higher quality of glycosides for pharmaceutical approaches.